PENGARUH PROFITABILITAS TERHADAP PEMBAYARAN DIVIDEN PADA PERUSAHAAN PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2017 - Noorsyah Adi Noer Ridha (Scientia Regendi, 2020)
This research focusing on profitability and dividend payment. Has purpose to determine how profitability on dividend payment In Retail Trading Companies Listed In The Indonesia Stock Exchange Period 2012– 2017. This observation research unit is financial statements of retail trading companies listed in Indonesia Stock Exchange category department store period 2012-2017 which amounted to 18 samples and using sampling techniques in the purposive sampling. This research use descriptive method, a method that illustrates how the profitability and dividend payment In Retail Trading Companies Listed In The Indonesia Stock Exchange Period 2012– 2017, and of the verification method that aims to test the hypothesis that has been formulated previously. Analysis of the data was used path analysis. To process data, the authors used SPSS Windows Version 23.0 so that the resulting data more quickly and accurately. The results of research stated that there is a significant positive effect of transformational profitability on dividend payment In Retail Trading Companies Listed In The Indonesia Stock Exchange Period 2012– 2017.